Preformulation characterisation of zeolite core materials in biocontrol products - Bunt, C.R.; Stelting, S.A.; Wright, D.A.; Swaminathan, J. (New Zealand Plant Protection, 2010)
Bioshield is a unique biocontrol agent that is used for control of the New Zealand grass grub (Costelytra zealandica) It consists of a core of zeolite with a biopolymer coating containing the bacterium Serratia entomophila Assessments of various zeolites (Z1BC Z1BDW Z1CG and Z1BI from New Zealand (NZZs) and AUFM 4/1 and AUZB from Australia (AZs)) were carried out prior to formulation Physical characteristics such as friability and water absorption and sorption were measured and success of bacterial coating was assessed by light microscopy and differential staining scanning electron microscopy (SEM) and cell loading (cfu/g) Friability assessment of NZZs found approximately 5 mass loss while AZs did not lose any mass NZZs absorbed approximately 30 w / w while AZs 10 w / w water Water sorption to zeolites appeared to monolayer in nature although NZZs and AZs monolayer adsorption isotherms appear to differ being type II and type I respectively SEM analysis showed the surface of NZZs to be porous and populated by colloidal particles while AZs appeared very smooth and lacking in surface features Success of coating S entomophila onto NZZs and AZs was confirmed by SEM enumeration and livedead staining